Peningkatan Derajat Kesehatan Masyarakat Desa Gung Pinto Melalui Intervensi Edukasi dan Pelayanan Kesehatan Terpadu: Enhancing Community Health Status in Gung Pinto Village Through Integrated Nutrition Education and Health Services Intervention - Febriyanti, Eka; Zambak, Muhammad Fitra; Saragih, Syaiful Amri; Hadipramana, Josef (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Public health challenges in rural areas of Indonesia are often influenced by low nutrition literacy, suboptimal clean and healthy living behaviors (CHLB), and limited access to healthcare services. This community engagement program aimed to improve nutrition literacy, promote preventive health behaviors, and facilitate early detection of health problems among residents of Gung Pinto Village, Karo Regency. The intervention was conducted on July 24, 2025, at the village hall, involving 30 participants from various age groups. The activities included balanced nutrition and CHLB education through interactive lectures and group discussions, as well as anthropometric measurements, physical examinations, and free medical treatment provided according to medical indications. Results revealed that most participants had a waist circumference above the standard threshold (80%), indicating central obesity, alongside complaints of gastritis/dyspepsia (20%), hypertension (6.7%), acute respiratory infections (3.3%), and mild neuralgia (6.7%). The combination of balanced nutrition and CHLB education, along with health screening and medical services, effectively increased awareness and facilitated the early identification of health issues. These findings underscore the need for integrated, context-specific public health approaches that align with Sustainable Development Goal (SDG) target three on good health and well-being.